Consequences of coronavirus infections for primitive and mature hematopoietic cells: new insights and why it matters. Issue 4 (July 2021) - Ropa, James; Trinh, Thao; Aljoufi, Arafat; Broxmeyer, Hal E.
Abstract : Purpose of review: In recent history there have been three outbreaks of betacoronavirus infections in humans, with the most recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; causing Coronavirus disease 2019 [COVID-19]) outbreak leading to over two million deaths, with a rapidly rising death toll. Much remains unknown about host cells and tissues affected by coronavirus infections, including the hematopoietic system. Here, we discuss the recent findings examining effects that coronavirus infection or exposure has on hematopoietic cells and the clinical implications for these effects. Recent findings: Recent studies have centered on SARS-CoV-2, demonstrating that hematopoietic stem and progenitor cells and mature immune cells may be susceptible to infection and are impacted functionally by exposure to SARS-CoV-2 Spike protein. These findings have important implications regarding hematologic complications arising from COVID-19 and other coronavirus-induced disease, which we discuss here. Summary: Infection with coronaviruses sometimes leads to hematologic complications in patients, and these hematologic complications are associated with poorer prognosis. These hematologic complications may be caused by coronavirus direct infection or impact on primitive hematopoietic cells or mature immune cells, by indirect effects on these cells, or by a combination thereof. It is important to understand how hematologic complications arise in order to seek new treatments to improve patient outcomes.